Characterization of iucA and iucC genes of the aerobactin system of plasmid ColV-K30 in Escherichia coli. - de Lorenzo, V (1986)
A cloned 8.3-kilobase-pair DNA fragment carrying all the genes (iucABCD iutA) of the aerobactin iron transport system of plasmid pColV-K30 was subjected to in vitro mutagenesis to afford mutant genes iucA, iucC, and iucA iucC. Complementation analyses and identification of aerobactin precursors accumulated by Escherichia coli cells harboring the different constructions allowed assignment of the iucA and iucC genes to discrete steps in biosynthesis of the siderophore from N epsilon-acetyl-N epsilon-hydroxylysine and citrate. Plasmid pVLN10, a derivative carrying a DNA fragment complementing an iucC mutation, expressed in a minicell system a single 62,000-dalton protein as the product of this gene.